The prevalence and correlates of low resilience in patients prior to discharge from acute psychiatric units in Alberta, Canada - Ernest Owusu; Wanying Mao; Reham Shalaby; Hossam Eldin Elgendy; Belinda Agyapong; Ejemai Eboreime; Mobolaji A. lawal; Nnamdi Nkire; Yifeng Wei; Peter H. Silverstone; Pierre Chue; Xin-Min Li; et al. (BMC Psychiatry)
Abstract Background Many people experience at least one traumatic event in their lifetime. Although such traumatic events can precipitate psychiatric disorders, many individuals exhibit high resilience by adapting to such events with little disruption or may recover their baseline level of functioning after a transient symptomatic period. Low levels of resilience are under-explored, and this study investigates the prevalence and correlates of low resilience in patients before discharge from psychiatric acute care facilities. Methods Respondents for this study were recruited from nine psychiatric in-patient units across Alberta. Demographic and clinical information were collected via a REDCap online survey. The brief resilience scale (BRS) was used to measure levels of resilience where a score of less than 3.0 was indicative of low resilience. A chi-square analysis followed by a binary logistic regression model was employed to identify significant predictors of low resilience. Results A total of 1,004 individuals took part in this study. Of these 35.9% were less than 25 years old, 34.7% were above 40 years old, 54.8% were female, and 62.3% self-identified as Caucasian. The prevalence of low resilience in the study cohort was 55.3%. Respondents who identified as females were one and a half times more likely to show low resilience (OR = 1.564; 95% C.I. = 1.79–2.10), while individuals with ‘other gender’ identity were three and a half times more likely to evidence low resilience (OR = 3.646; 95% C.I. = 1.36–9.71) compared to males. Similarly, Caucasians were two and one-and-a-half times respectively more likely to present with low resilience compared with respondents who identified as Black (OR = 2.21; 95% C.I. = 1.45–3.70) or Asian (OR = 1.589; 95% C.I. = 1.45–2.44). Additionally, individuals with a diagnosis of depression were significantly more likely to have low resilience than those with a diagnosis of either bipolar disorder (OR = 2.567; 95% C.I. = 1.72–3.85) or schizophrenia (OR = 4.081;95% C.I. = 2.63–6.25). Conclusion Several demographic and clinical factors were identified as predictors of likely low resilience. The findings may facilitate the identification of vulnerable groups to enable their increased access to support programs that may enhance resilience. Clinical trial registration clinicaltrials.gov, NCT05133726. Registered on the 24th of November 2021.